The Relationship between the Intensity of Tahajud Prayer and the Stress Level of Grade IX Students of Istiqomah Sambas Sambas Boarding School Purbalingga - Novitri, Ersa Agriana; Fuad, Wijayanti; Basuki, Rochman (Buletin Farmatera, 2025)
Abstract: Stress can affect mental states in adolescents, especially students. Stress in Purbalingga Regency has a prevalence of 62.5%. This condition can be affected by a variety of factors. Islam provides one of the solutions to relieve stress, namely by getting closer to Allah, one of which is by performing tahajud prayers. Most studies have looked more at stress in college students than in college students. This study aims to analyze the relationship between the intensity of tahajud prayer and the stress level of grade IX students of Istiqomah Sambas Boarding School Purbalingga. The method used was observational analytics with a cross-sectional approach. The technique in the study was a total sampling with a total of 118 respondents and 92 respondents were included in the inclusion and exclusion criteria. The intensity of tahajud prayer was measured by a questionnaire on the intensity of tahajud prayer and the level of stress with a DASS scale of 42. Relationship analysis using the Spearman rank test. The intensity of tahajud prayer was mostly included in the good category, which was 36 students (39.1%) and the stress level of the majority of students was included in the normal category, which was 30 students (32.6%). The Spearman rank test showed a p-value of 0.000 and a correlation coefficient value of -0.743. There is a significant relationship between the intensity of tahajud prayer and the level of stress with the direction of a negative correlation, which means that the higher the intensity of tahajud prayer, the lower the student's stress level.